2021
DOI: 10.1002/jcc.26488
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the electrostatic σ‐hole picture of halogen bonding using minimal models and the interacting quantum atoms approach

Abstract: Among the different noncovalent interactions, halogen bonds have captured wide attention in the last years. Their stability has been rationalized in electrostatic terms by appealing to the σ-hole concept, a charge-depleted region that is able to interact favorably with electron rich moieties. This interpretation has been questioned, and in this work a set of anionic halogen model systems are used to shed some light on this issue. We use the interacting quantum atoms method, which provides an orbital invariant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…Among the established concepts on noncovalent intermolecular interactions, the σ‐hole model and its implications have been controversially discussed in recent years, especially in the context of halogen bonding [42–44] . While all studies agree on the fact that a depletion of electron density opposite of a sigma bond leads to a fairly strong interaction that is strongly directional, [45,46] different analysis tools indicate that it could either be regarded as electrostatic or as charge‐transfer including orbital interactions [47] . For the interaction of heavy pnictogen atoms and the π‐system, as discussed in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the established concepts on noncovalent intermolecular interactions, the σ‐hole model and its implications have been controversially discussed in recent years, especially in the context of halogen bonding [42–44] . While all studies agree on the fact that a depletion of electron density opposite of a sigma bond leads to a fairly strong interaction that is strongly directional, [45,46] different analysis tools indicate that it could either be regarded as electrostatic or as charge‐transfer including orbital interactions [47] . For the interaction of heavy pnictogen atoms and the π‐system, as discussed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42 , 43 , 44 ] While all studies agree on the fact that a depletion of electron density opposite of a sigma bond leads to a fairly strong interaction that is strongly directional,[ 45 , 46 ] different analysis tools indicate that it could either be regarded as electrostatic or as charge‐transfer including orbital interactions. [47] For the interaction of heavy pnictogen atoms and the π‐system, as discussed in ref. [10] , a thorough analysis of the angle‐dependance of the interaction energies, however, showed that the potential energy surfaces appear very flat.…”
Section: Resultsmentioning
confidence: 99%
“…Brinck and Borrfors studied a series of halogen bonded complexes (R–Br···Br – and R′–CC–Br···Br – where R is a substituted methyl group) and showed that the halogen-bonding strength correlates linearly with the interaction energy from a point-charge model by replacing Br – with a point charge. Subsequently, they concluded that “the halogen bond can be described accurately by electrostatics and polarization without any need to consider charge transfer.” But there have been negative correlations between maximum electrostatic potentials and interaction energies even when polarization is considered in the literature. , In fact, there have been profound theoretical and experimental studies, including ours, confirming the crucial or even dominating role of charge transfer interaction in halogen bonding. For instance, Wolter and Bickelhaupt compared the halogen bonding in D–X···A – and hydrogen bonding in D–H···A – (D, X, and A are halogen elements) and found that apart from the classical electrostatic attraction, there is substantial HOMO–LUMO interactions between the lone pair of A and the σ* orbital of the D–X or D–H bond . In other words, there is considerable charge transfer interactions from A – to D–X/D–H in both types of bonding.…”
Section: Introductionmentioning
confidence: 81%
“…In an octameric synthon, the Although the electrostatic model continues to be useful in rationalizing the halogen bonding, 111 our results support the need to consider the weak nonelectrostatic interactions for this purpose. 42,112…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Albeit the presence of σ-holes, the Br···Br interactions present in the synthons have destabilizing or nearly zero Coulombic components according to the IQA analysis. Although the electrostatic model continues to be useful in rationalizing the halogen bonding, our results support the need to consider the weak nonelectrostatic interactions for this purpose. , …”
Section: Resultsmentioning
confidence: 99%